The Ideational Meanings of Multimodal Texts Presented in an EFL Textbook - Dea Putri Rafelina; Budi Hermawan (Siliwangi University, 2022)
This study explores the ideational meanings of multimodal texts in an EFL textbook entitled â€œBahasa Inggris: When English Rings a Bellâ€. This study aims to describe the meanings of visual and verbal modes from ideational aspects. The visual modes were analyzed by using Visual Grammar Design framework (Kress van Leeuwen, 2006). Meanwhile, the verbal modes were analyzed using Systemic Functional Grammar theory focusing on the Transitivity system (Halliday, 1994). The ideational aspects of this study focus on components like participants, processes and circumstances. This study applied Systemic Functional Multimodal Discourse Analysis (henceforth SF-MDA) methodology. The findings of this study found that the dominant process types used in realizing the ideational meaning of the verbal text is relational process. Meanwhile, the ideational meaning of visual text is realized mostly through speech process. This study showed that the presentation of multimodal texts in the EFL textbook is relevant to the teaching and learning activity for the Junior high school students.Â Keywords: multimodality, ideational meaning, systemic functional grammar, multimodal analysis